KEARIFAN LOKAL MEMPENGARUHI GOOD GOVERNANCE - Indra Prasetya; Priyatno Harsasto; Kushandajani . (Journal of Politic and Government Studies, 2016)
Local wisdom be considered as the identity that determines the dignity a society in their community. In other words, an embodiment which is manifested through the way of life, behavior, and knowledge of activities performed by the local people to answer problems in fulfilling the life, and maintain their cultural matters. .This concept of these is a philosophy in every motion public life in Tabanan, including in political life. This research aims to determine the role of local knowledge in the government to achieving good governance in order to reduce the rate of corruption in Tabanan by explain the implementation of local knowledge on public policy and its actualization in the practice of government.This research uses the method of qualitative study, with data collection method through the interviews and literature. The data sources used in this reseach was primary and secondary data which reviewed and analyzed by descriptive approach.The results of this research is the values of local wisdom in tabanan are the basis of the principles of public life, including in the governance aspect. Parameters that indicate the values of local wisdom in Tabanan government contained on accountability, transparency and public participation. That point was characteristic in efforts to achieve good governance in Tabanan. Some empirical manifestations of local wisdom contained in the actualization of governance practices in achieving good governance in order to reduce the rate of corruption include making the procurement of goods and services policy in an accountable and transparent and make a model of electronic transactions and the transparency of budget management so that people can participate oversee groove in and out of government funds.There needs to be planting the thought of democracy based on ethics and morality in order to end the political taboo in most societies tabanan. .The form of relation the village community pakraman with village administration agency as an extension “hand” the country better have been decentralized than centralized as a form of recognition of the diversity of the village which has the right to manage themselves. By doing so, democratic culture of the pakraman village can develop and grow harmoniouslyKeywords: Local Wisdom, good governance, corruption